PENGARUH METODE PEMBELAJARAN MNEMONIC BERBASIS VIDEO TERHADAP HASIL BELAJAR IPAS KELAS IV SDN 1 BANGODUA - Setyaningsih, Vani; Susilawati; Erna Labudasari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the use of video-based mnemonic learning methods along with developments in science and technology. The aim of this research is to determine whether there is an effect of using video-based mnemonic learning methods on science learning outcomes in class IV students at SDN 1 Bangodua. This research was carried out at SDN 1 Bangodua with a sample size of 20 students using the OneGrup Pretest Posttest Design technique. The approach used is a quantitative approach with experimental methods. The data collection instruments in this research were test sheets and questionnaires. The hypothesis proposed in this research is that there is an influence of the video-based mnemonic learning method on science learning outcomes in class IV students at SDN 1 Bangodua. Data analysis techniques use normality tests, homogeneity tests, and hypothesis tests (t-test). The results of the research showed that student learning outcomes in science subjects using conventional learning models were with an average score of 38. Learning outcomes in science subjects using video-based mnemonic learning methods were with an average score of 80. The results of the t-test obtained a significance level of 0.000. This proves that the video-based mnemonic learning method has a significant influence on learning outcomes in science and technology subjects in class IV SDN 1 Bangodua.